COVID-19 presenting as right flank pain in a postpartum woman: A case report. (September 2021) - Chegini, Venus; Hosseini, Reihaneh; Zarei, Neda; Chegini, Victoria; Aghajani, Faezeh; Nakhostin-Ansari, Amin; Kasraei, Sara
Abstract: Introduction: Patients with COVID-19 infection may present a wide range of symptoms that make its diagnosis challenging, especially in patients with underlying conditions. Presentation of case: A 30-year-old postpartum woman presented to the Emergency Department (ED) of Arash Women Hospital with right flank pain. Physical examination revealed tachycardia and decreased sounds in the base of the lung. Chest CT scan demonstrated patchy consolidations in bases of the lungs in favor of COVID-19 infection. The patient underwent pharmacotherapy with Remdesivir, steroid, and interferon beta-1a for eight days and was discharged in a good condition. Discussion: This study suggests that involvement of lungs' bases may be associated with gastrointestinal symptoms such as abdominal or flank pain in the COVID-19 patients. It makes the diagnosis difficult in a scenario such as the described patient in our study where there may be other differential diagnoses correlating with the patient's clinical course. Conclusion: COVID-19 should be in the differential diagnosis of any patient presenting to ED with relevant complaints. Correct and immediate diagnosis is critical for proper treatment and isolation of patients with COVID-19. Highlights: COVID-19 may have several presentations, which make the diagnosis process challenging. This case report presents a postpartum woman with COVID-19, which presents as right flank pain. COVID-19 should be in the differential diagnosis of any patient presenting to ED with relevant complaints.